2021
DOI: 10.3390/s21051669
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Distribution Detection of Human Activity Recognition with Smartwatch Inertial Sensors

Abstract: Out-of-distribution (OOD) in the context of Human Activity Recognition (HAR) refers to data from activity classes that are not represented in the training data of a Machine Learning (ML) algorithm. OOD data are a challenge to classify accurately for most ML algorithms, especially deep learning models that are prone to overconfident predictions based on in-distribution (IIN) classes. To simulate the OOD problem in physiotherapy, our team collected a new dataset (SPARS9x) consisting of inertial data captured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 66 publications
(120 reference statements)
0
24
0
Order By: Relevance
“…The authors collected a new data set (SPARS9x) from inertial smartwatch sensors worn by 20 volunteers, first performing supervised physical exercises and, after, performing other unrelated physical movements (OOD). From this analysis, the authors showed that traditional algorithms outperform deep learning algorithms for this particular case of OOD detection for HAR [7].…”
Section: Contributed Papersmentioning
confidence: 97%
See 2 more Smart Citations
“…The authors collected a new data set (SPARS9x) from inertial smartwatch sensors worn by 20 volunteers, first performing supervised physical exercises and, after, performing other unrelated physical movements (OOD). From this analysis, the authors showed that traditional algorithms outperform deep learning algorithms for this particular case of OOD detection for HAR [7].…”
Section: Contributed Papersmentioning
confidence: 97%
“…Another work devoted to the human activity recognition (HAR), using smartwatch inertial sensors, was presented by the authors of [7]. The authors study the performance of three algorithms for the out-of-distribution (OOD) detection of activity classes data that are not present in the training data of the ML [7].…”
Section: Contributed Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple works specifically aimed at assessing therapy exercises and providing feedback [25][26][27]. However, the current approaches can only provide automatic motion detection or assessment based on wearable devices or video input.…”
Section: Assisting Physical Rehabilitationmentioning
confidence: 99%
“…The advantage of this methodology is that the embedding method can be fitted or trained to a large dataset in advance, while user-specific interrogation can be rapidly accomplished in a de novo fashion via feature extraction through the pre-trained embedder, with the resulting embedding subsequently used to perform classification and/or characterization. Further benefits of this approach include the capacity to incorporate novel activity classes without model re-training, and identify out-of-distribution (OOD) activity classes (i.e., samples drawn from class distributions previously unseen in classifier training), thereby supporting an open-set activity recognition framework [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%